1999
DOI: 10.1038/sj.jidsp.5640184
|View full text |Cite
|
Sign up to set email alerts
|

Sunscreen Effects on UV-Induced Immune Suppression

Abstract: In order to protect the public against the adverse effects of sunlight, the scientific, medical, and particularly the dermatologic community has promoted "safe sun exposure." This strategy includes sun avoidance whenever possible, wearing hats and other protective clothing and/or devices, such as sunglasses, and extensive use of sunscreens. Sunscreen efficacy is determined by measuring the ability of the sunscreen to block ultraviolet (UV)-induced erythema (sun protection factor or SPF), and most sunscreen for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…However, it has been shown that both DNA damage and immunosuppression are induced by UVR at the suberythema doses (7). It has also been demonstrated that some UVR‐induced genetic damage and immunosuppression occur in spite of sunscreen uses (8). Therefore, development of highly effective and efficacious photopreventive products has become a top priority in the field of dermatology.…”
mentioning
confidence: 99%
“…However, it has been shown that both DNA damage and immunosuppression are induced by UVR at the suberythema doses (7). It has also been demonstrated that some UVR‐induced genetic damage and immunosuppression occur in spite of sunscreen uses (8). Therefore, development of highly effective and efficacious photopreventive products has become a top priority in the field of dermatology.…”
mentioning
confidence: 99%
“…concluded that, based on the available data, sunscreens offer, at best, partial protection from UV‐induced immune suppression and that a product's immune‐protective capacity is probably less than its capacity to prevent erythema (i.e. IPF < SPF) 13 . However, most of these data were derived using sunscreens that filter mainly in the more erythemogenic UVB region (290–320 nm) and, to some extent, through the UVAII portion (320–340 nm) of the spectrum.…”
Section: Definition Of Terms and Abbreviations Commonly Used In Photomentioning
confidence: 99%
“…However, the most popular fluorescent sunlamp used in photoimmunology, the FS40, contains both short-wave UVB and UVC (4). The use of a cellulose acetate filter (Kodacelfilter) to block short-wave UV below 290 nm (4) can avoid this problem, but even with Kodacel-filtered FS40 sunlamps, there remains sufficient amounts of short-wave, highly potent immune-suppressing UV below 295-300 nm (Fig.…”
Section: Controversies Concerning Sunscreen Protectionmentioning
confidence: 99%
“…The ability of a sunscreen to protect against erythema, the so-called SPF, although well characterized may not be an adequate measure of a sunscreen's ability to protect against other biological endpoints, particularly immune suppression (4). Although there are many examples in the scientific literature regarding sunscreen protection against UV-in-…”
mentioning
confidence: 99%